2016
DOI: 10.1371/journal.pone.0152564
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use and the Risk of Parkinson's Disease: An Updated Meta-Analysis

Abstract: IntroductionIn response to the ongoing debate over the relationship between the use of statins and the risk of Parkinson's disease (PD), we performed a systematic review and meta-analysis of observational studies to examine their association.MethodsWe conducted a review of the literature using electronic databases supplemented by a manual search to identify potentially relevant case-control or cohort studies. Summary relative risk (RRs) and 95% confidence intervals (CIs) were calculated using a random-effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 31 publications
1
43
0
1
Order By: Relevance
“…In an adjusted model, PD was inversely associated with statin use (current or ever, OR = 0.56), but with marginal statistical significance (p = 0.07). This inverse association between PD and statin use has been previously observed in larger studies [5,7]. ET was not associated with statin use (current or ever); however, there was an inverse association in an analysis that assessed longer term use of statins.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In an adjusted model, PD was inversely associated with statin use (current or ever, OR = 0.56), but with marginal statistical significance (p = 0.07). This inverse association between PD and statin use has been previously observed in larger studies [5,7]. ET was not associated with statin use (current or ever); however, there was an inverse association in an analysis that assessed longer term use of statins.…”
Section: Discussionsupporting
confidence: 75%
“…However, long term statin use (≥ 5 years) was inversely associated with PD in a sample of 312 PD patients and 342 controls from three rural California counties [5]. Attempting to summarize data from eleven studies, a recent meta-analysis concluded that statin use was associated with a reduced risk of PD (summary relative risk = 0.81, 95% confidence interval = 0.71 – 0.92) [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Three-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors (statins) have been theorized to have neuroprotective effects in neurodegenerative diseases, such as Alzheimer's and Parkinson's diseases. [7][8][9][10] In HD animal models, statins are known to upregulate nitric oxide synthase, reduce the inflammatory response, and decrease oxidative stress. [11][12][13] This antioxidative effect of statins is particularly relevant for HD, in which reactive oxygen species are thought to impact the AMD.…”
Section: Introductionmentioning
confidence: 99%
“…Greater than 50% of subjects participating in clinical trials of Alzheimer's disease are positive for ApoE4 [17]. Similarly, two meta-analyses have reported a correlation between statin therapy and a reduced risk in the development of Parkinson's disease [18,19]. Rosuvastatin, a widely prescribed HMG-CoA reductase inhibitor, has been used for the treatment of dyslipidemia (LDL-C) and has been proven to be more effective in comparison to other members of its class [20].…”
Section: Introductionmentioning
confidence: 99%